PERBEDAAN LAMA WAKTU PEMBERIAN PAKAN MENGANDUNG JINTAN HITAM TERHADAP KELANGSUNGAN HIDUP dan PERTUMBUHAN IKAN GABUS yang DIUJI TANTANG Aeromonas hydrophila - Mery Valeta; Ade Dwi Sasanti; Yulisman . (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACTOne of problem on snakehead culture is lower value of survival and growth because of disease occurence. The aim of this research was to know the effect of different feeding time duration on survival and growth rate of snakehead fed by black cumin challenged by A.hydrophila. This research conducted from August until September 2015 in Laboratorium Budidaya Perairan, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University. The research method used Completely Randomized Design (CRD) with seven treatments and three replications : P1(fed without black cumin during 30 days no challenged), P2 (fed without black cumin during 30 days challenged by A. hydrophila), P3 (fed contain black cumin during 30 days no challenged), P4 (fed contain black cumin during 30 days challenged by A. hydrophila), P5 (fed contain black cumin during 21 days challenged by A. hydrophila), P6 (fed contain black cumin during 14 days challenged by A.hydrophila), and P7 (fed contain black cumin during 30 days challenged by A. hydrophila). The result of the research showed that snakehead fed by black cumin during 14 days (P6) challenged by A. hydrophila showed the highest value of survival rate, and growth, each sequentially were 93.33%, 5.28 g, and 1.32 cm. Keywords : snakehead, black cumin, survival rate, growth